The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph19020840
|View full text |Cite
|
Sign up to set email alerts
|

Development of 222Rn Emanation Sources with Integrated Quasi 2π Active Monitoring

Abstract: In this work, a novel approach for the standardization of low-level 222Rn emanation is presented. The technique is based on the integration of a 222Rn source, directly, with an α-particle detector, which allows the residual 222Rn to be continuously monitored. Preparation of the device entails thermal physical vapor deposition of 226RaCl2 directly onto the surface of a commercially available ion implanted Si-diode detector, resulting in a thin-layer geometry. This enables continuous collection of well resolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Since the mechanism causing the release of radon consists of a combination of two processes, on the one hand the recoil of the nuclei resulting from alpha decay and on the other hand the diffusion processes, the amount of radon released usually correlates with environmental parameters, such as relative humidity and temperature, since these influence the effective diffusion coefficient. To investigate these dependencies, novel sources have been developed at PTB with the metrological possibility of continuous determination of the emanation [8]. Thus, it can be shown that at low penetration depth of the ionimplanted 226 Ra, there is no measurable dependence of the emanation on the ambient humidity and only a small dependence on the temperature [9].…”
Section: New Activity Standardsmentioning
confidence: 99%
“…Since the mechanism causing the release of radon consists of a combination of two processes, on the one hand the recoil of the nuclei resulting from alpha decay and on the other hand the diffusion processes, the amount of radon released usually correlates with environmental parameters, such as relative humidity and temperature, since these influence the effective diffusion coefficient. To investigate these dependencies, novel sources have been developed at PTB with the metrological possibility of continuous determination of the emanation [8]. Thus, it can be shown that at low penetration depth of the ionimplanted 226 Ra, there is no measurable dependence of the emanation on the ambient humidity and only a small dependence on the temperature [9].…”
Section: New Activity Standardsmentioning
confidence: 99%
“…Since the mechanism that causes the release of radon consists of a combination of two processes, on the one hand the recoil of the nuclei as a result of alpha decay and on the other hand the diffusion processes, the amount of radon released usually correlates with environmental parameters, such as relative humidity and temperature, since these influence the effective diffusion coefficient. In order to investigate these dependencies, novel sources were developed at PTB with the metrological possibility of continuous determination of the emanation [8]. Thus, it could be shown that at low penetration depth of the ionimplanted 226 Ra there is no measurable dependence of the emanation on the ambient humidity and only a small dependence on the temperature [9].…”
Section: New Activity Standardsmentioning
confidence: 99%
“…Implementing large-scale radon monitoring networks to provide concentration data for environmental sciences and ensuring their comparability requires calibration techniques for radon monitors in this concentration range, which is one of the tasks of the EU traceRadon project. Mertes et al [ 8 ] presented a novel approach to standardizing low-level radon emanation. The technique was based on integrating the radon source directly with an -particle detector to facilitate the continuous monitoring of radon residues.…”
mentioning
confidence: 99%